(untitled) (Proceedings of International Educators Conference, 2023)
This article presents the beginning of the Battle of Chaldiron, the largest conflict between the two powerful Ottoman and Safavid empires in the Middle East at the beginning of a new era, and its results. The result of this war showed that the Ottoman Empire was the most powerful country and that the Safavids stopped dealing with the West.